TEXT AS THE MAIN FORM OF KNOWLEDGE CONTROL STUDENTS WITHIN THE CREDIT-MODULAR LEARNING SYSTEMS (Pedagogy of Higher and Secondary Education, 2007)
The article deals with some peculiarities in using test-control as the means of mostly objective grading of students’ knowledge.